Life cycle theory of dividends: a review of literature - Hussain, Haroon; Md Rus, Rohani; Al‐jaifi, Hamdan Amer Ali (Universiti Malaysia Perlis, 2018)
Purpose: This study aimed at reviewing life cycle theory of dividends based on summarized empirical evidences provided in the previous studies.Design/methodology/approach: The key theoretical and empirical studies on life cycle theory of dividends have been reviewed. Findings: It has been found in the review that more attention needs to be given to the role of governance in the life cycle theory of dividends. Corporate governance indicators change with the life cycle stage of the firm and governance provisions are adopted based on firm characteristics. Furthermore, culture and investor protection vary across countries and their impact depends on firm life cycle. Thus, more flexible models should be designed to capture the role of individual governance measures in the pay‐out policy based on firm characteristics, national culture and investor protection under life cycle theory of dividends.Originality/value: Through this study, the role of culture and investor protection in life cycle theory of dividends has been emphasized and the necessity of considering such studies has been specified for researchers. Limitations: Since the life cycle theory of dividends was the very focus of the current study, other theories of dividend policy have not been paid heed to. Paper type: Literature review